Self-care at the margins of healthcare: 'Malingering' and 'self-neglecting' cystic fibrosis patients. (May 2014) - Greenop, Daz; Glenn, Sheila
This article focuses on two small groups of adult cystic fibrosis patients (from a larger sample) who, for very different reasons, do not self-care. These two distinct counter-narratives may be located at the extreme margins of a continuum of responses to the demands of body and society. They are described and contrasted here as controlled and chaotic and are dominated by 'supportive' and 'unsupportive' voices respectively. The patient's own voice, by way of contrast, is often silent or silenced by these dominant others. Despite the loss of self that becomes evident in these narratives, limited sites of resistance remain as both sets of participants sought to disrupt, parody and subvert expectations to self-care with stories of 'malingering' and 'self-neglect'. Finally, some practical suggestions are provided for social workers to engage patients whom might otherwise be regarded as 'difficult'.